Longitudinal changes in bodyweight, body condition, and muscle condition in ageing pet cats: findings from the Cat Prospective Ageing and Welfare Study - Pye, Christine R.; Dowgray, Nathalie J.; Eyre, Kelly; Pinchbeck, Gina; Biourge, Vincent; Moniot, Delphine; Comerford, Eithne; German, Alexander J. (Frontiers in Veterinary Science, 2025)
Body composition metrics such as bodyweight, body condition score (BCS) and muscle condition score (MCS) can be readily recorded as part of veterinary examinations in ageing cats. However, the description of how these parameters change with age, whilst accounting for sex and age-related morbidity, is limited. The aim of this prospective cohort study was to evaluate age, sex and health-related changes in bodyweight, BCS and MCS in client-owned pet cats. A total of 1,231 veterinary examinations were performed on 209 pet cats aged 6.7–16.4 years enrolled on the Cat Prospective Ageing and Welfare Study. Cats were followed every 6 months for up to 7 years. Mixed-effects models using natural cubic splines were applied to investigate non-linear age-related changes, adjusting for sex and disease status. All three metrics showed significant non-linear associations with age. Bodyweight increased slightly from age 7 to 10 (estimated marginal mean 4.77–4.82 kg) before decreasing to 4.30 kg by age 16 years. Body condition score also increased slightly during middle age, before declining after age 10.5 years. The combined MCS (maximum 30 points, based on 10 skeletal landmarks) decreased gradually from 30 points to 28 points between ages 7 and 10, before decreasing at a greater rate to 15 points by age 16. After age 10, the cats had a greater probability of mild muscle loss than no muscle loss, and by age 14, they were more likely to be underweight than obese. Male cats were heavier and had 2.8 times greater odds of being overweight (p = 0.002); there were no sex differences in MCS. Cats that developed chronic disease had a greater age-related decline in all three metrics. Associations with various chronic diseases were identified, including a positive association between orthopaedic abnormalities and bodyweight. These findings indicate that muscle loss begins before middle age in cats, whilst loss of body condition and bodyweight begins after age 10. The results also outline the importance of monitoring body composition metrics in veterinary examinations of ageing cats.